Multifunctional Control Strategy for Asymmetrical Cascaded H-Bridge Inverter in Microgrid Applications - Mortezaei, A.; Simoes, M. Godoy; Bshait, A. S. Bu; Curi Busarello, T. D.; Marafao, F. P. [UNESP]; Al Durra, A.; IEEE (Ieee, 2015)
A multitask Asymmetrical Cascaded H-Bridge Multilevel Inverter (ACHMI), suitable for microgrid systems with possible unbalanced and nonlinear loads, is presented. The primary advantage of ACHMI is to produce a staircase output voltage utilizing unequal DC voltages such as Solar cells, fuel cells, batteries on the individual H-bridge cells. The ACHMI provide a large number of output steps without increasing the number of DC voltage sources and components where the difference between output waveform and reference sinusoidal waveform would be reduced. For grid connected mode of operation, the control strategy is based on the Conservative Power Theory (CPT), providing simultaneous functionalities for the Distributed Generation (DG) system to inject its available energy, compensate the load current distortions and allow a smooth transition between grid-connected and islanded modes of operation. For the islanded mode of operation, regulation of load voltage in a wide range of load conditions is presented. The Conservative Power Theory decompositions provides decoupled power and current references for the inverter control in abcframe, offering a very flexible, selective and powerful strategy for the DG control system. The principles supporting the developed control strategy are discussed and analyzed and the effectiveness of the control is demonstrated through digital simulations conducted by means of PSIM.
Keywords: Conservative Power Theory; Digital Control; Distributed Generation; Microgrid; Multilevel inverter; Power Quality Improvement